I feel sick! : a Little Princess story - Ross, Tony (Andersen Press : Distributed in the United States by Lerner Publishing Group, Inc., 2015)
Claiming to be too ill to do chores or go to school, the Little Princess makes a miraculous recovery when a party invitation arrives.